Ecological trial of the rostov rice varieties in the Krasnodar territory - P. I. Kostylev; М. А. Ladatko; Е. V. Krasnova; I. A. Zeleneva; B. V. Foliyants; А. V. Aksenov (Зерновое хозяйство России)
In modern rice growing, the development of new varieties and their rapid introduction into agricultural production is of great importance. Every year the Federal Research Center of Rice and the ARC “Donskoy” develop more productive rice varieties with improved tolerance to unfavorable biotic, abiotic stress factors, with various nutritional qualities of seeds. Any variety responds differently to a variety of agro-ecological conditions, forming different productivity, as the main indicator of cost and demand in production. The current paper has presented the results of ecological variety testing of four rice varieties conducted in 2020 on the fields of ‘Krasnoarmeisky’ and ‘Krasnaya’ located in the Krasnoarmeisky district of the Krasnodar Territory. Each variety was identified on variability of productivity and number of plants per unit area. The productivity of rice varieties varied significantly depending on the variant of the trial (2.93–8.79 t/ha). The variety ‘Kapitan’ significantly surpassed the standard variety ‘Rapan’, when sown after rice and alfalfa, but was at the same level in the agro-ameliorative field. The variety ‘Kapitan’ when sown after ‘AMP’ (high check) formed the maximum productivity of 8.79 t/ha in the background variant and 8.66 t/ha when topdressing with N30. It was due to the high resistance of the variety ‘Kapitan’ to local species of blast in difference from other varieties. Rice stand ranged from 70.5 to 519.0 pcs/m2. The variability between the varieties within the variant was medium (CV = 11.1–19.2%), and between the experimental variants it was high (CV = 59.0–71.3%). For cultivation in the Krasnodar Territory there has been recommended the rice variety ‘Kapitan’, developed by the ARC “Donskoy” together with FRC of rice, which has shown fairly high productivity with little variability.